Chronic Kidney Disease: A Case Report - Sonal Dhobe1 , Vaishali Tembhare2 , Ruchira Ankar3 , Savita Pohekar4, Samruddhi Gujar5 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Chronic kidney disease can occur in mostly those patient which having a history of hypertension anddiabetes, this disease also known as a chronic renal failure. In this disease condition kidney can decreasingthe rate of filteration or kidney function since month or a year. In the beginning period of Chronic KidneyDisease the person not showing any sign and symptoms about disease condition, after the months and yearpatient showing symptoms like nausea, vomiting, lethargy edema, confusion and loss of appetite. If theearly detection and treatment is not getting so the patient can goes in complication such as heart disease,hypertension, bone disease and anemia.1 Case Report: The female patient name is Rashida khan 63 yearold religion by Muslim lived in the yawatmal. She was admitted in the AVBRH with the chief complaintof breathing difficulty, fever, nausea and vomiting, swelling on both legs, lethargy weakness since 10 days.She having a history of HTN since 5 year and freshly diagnosed as DM2.Conclusion: This case presentedhow the prolong history of HTN which is uncontrollable causing the DM2 and it can leads to CKD. Thefirstly clinical presentation of the patient providing information about the history of HTN and DM2 and thelaboratory studies suggested a reducing function of kidney. So the patient sign, symptoms and the laboratoryvalues showing the condition of patient kidney with increasing volume of kidney, breathing difficulty,moderate anemia and uremia. Early detection of the HTN and DM2 and their management in early stage,also the modification in lifestyle and diet can help to reduce the chances of occurring Chronic KidneyDisease. Patient also have to complete the given treatment and counseling about the disease condition, andthe problem get solved by taking proper treatment.